Impact of Bilateral and Unilateral Exercises on Acute Enhancement of Horizontal Jump Performance in Professional Soccer Players - Sánchez, Javier Sánchez (2024)
Objective: To analyze the effect of activation through bilateral or unilateral strength and plyometric exercises on horizontal jump performance. Methodology: The study involved 15 highly trained male soccer players (age, 24.7 ± 3.1 years; height, 181.2 ± 4.7 cm; weight, 79.7 ± 3.4 kg) from the same team competing in the national league. Their regular training routine consisted of 4 sessions and 1 competitive match per week. Participants performed 1 control protocol (CON) and 3 activation protocols following a counterbalanced design based on specific soccer exercises (SIN), bilateral (BIL), and unilateral (UNI) strength and plyometric exercises. After each protocol, players underwent the horizontal jump test (HZB). Results: The repeated measures ANOVA revealed significant positive effects on HZB for the SIN (p<0.01; diff = 2.95(2.00) %), BIL(p<0.01; diff = 3.22(2.61) %), and UNI (p<0.01; diff = 6.80(3.40) %) protocols compared to CON. Furthermore, HZB was significantly higher after the UNI protocol than after SIN (p<0.01; diff = 3.74(2.62) %) and BIL (p<0.01; diff = 3.47(1.94) %). Individual response analysis reflected positive effects on HZB for SIN, BIL, and UNI compared to CON, while 89 % of players showed better HZB performance after UNI than after BIL. Conclusions: Activation incorporating unilateral strength and plyometric stimuli has a greater positive effect on horizontal jump capacity than activation involving general, soccer-specific, and bilateral exercises.